2006
DOI: 10.1080/10420150600703957
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of hydrogen released on the charge state of incident ions

Abstract: The behavior of polymers under heavy ion bombardment is of great interest. In the present study, hydrogen released from polypropylene (PP) and polyethylene terephthalate (PET) was investigated as a function of charge state (11 + , 14 + , and 25 + ) for 130 MeV 107 Ag ions. It was found that hydrogen released from the polymers varies as αq n , where n was found to be 2.98 and 1.94 for PP and PET, respectively, when compared with the value of ∼3.0 reported in the literature for different polymers and ion combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Halhammer et al [25] also reported the charge state dependence of projectiles guiding through nanocapillaries in PET. If we compare the value of exponent n = 2.1 from the present worked out problem to that reported earlier n = 2.98 for PP (13) we can easily conclude that the chances of hydrogen depletion are less from CH 2 bonds. Fujimoto et al [26] suggested that the hydrogen released as H + from CH or CH 2 may recombine with dangling carbon bonds.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Halhammer et al [25] also reported the charge state dependence of projectiles guiding through nanocapillaries in PET. If we compare the value of exponent n = 2.1 from the present worked out problem to that reported earlier n = 2.98 for PP (13) we can easily conclude that the chances of hydrogen depletion are less from CH 2 bonds. Fujimoto et al [26] suggested that the hydrogen released as H + from CH or CH 2 may recombine with dangling carbon bonds.…”
Section: Discussionsupporting
confidence: 70%
“…Heavier elements, molecules and radicals emitted during the ion irradiation were stopped with the help of a polypropylene film of thickness 26 µm kept before the detector. Further experimenttal details can be found in our earlier work [7,13].…”
Section: Experimental Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…to polymeric substances may be employed frequently to tailor their properties. The exposure of ion beam may create ion tracks in the polymers [1]. In addition to this, the ionizing radiations may also produce random fracture of main chain and braking of original bonds giving rise to the formation of free radicals, double/triple bonds, cross linking [2]- [8], carbon cluster formation [9] [10] and evolution of ionic species and gaseous components etc.…”
Section: Introductionmentioning
confidence: 99%